2014
DOI: 10.1088/0957-4484/25/49/495102
|View full text |Cite
|
Sign up to set email alerts
|

In vivo detection of magnetic labeled oxidized multi-walled carbon nanotubes by magnetic resonance imaging

Abstract: Functionalized carbon nanotubes (f-CNTs) have been widely used in bio-medicine as drug carriers, bio-sensors, imaging agents and tissue engineering additives, which demands better understanding of their in vivo behavior because of the increasing exposure potential to humans. However, there are limited studies to investigate the in vivo biodistribution and elimination of f-CNTs. In this study, superparamagnetic iron oxides (SPIOs) were used to label oxidized multiwalled carbon nanotubes (o-MWCNTs) for in vivo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Thus, CNTs were detected in the spleen and liver, but not in the lungs, kidney, and skin when administered intravenously; in this case, hematological or immunological toxicity was not observed [7]. In another study, at the same administration mode, the functional MWCNTs were found in the liver, kidney, and spleen, from which they were eliminated mainly in 4 days [6]. By magnetic resonance imaging, it was shown that, after intravenous injection to rats, SWCNTs are accumulated in the spleen (up to 7 days), liver (up to 2 days), and kidneys (up to 5 days), but not in the lungs and blood [8].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Thus, CNTs were detected in the spleen and liver, but not in the lungs, kidney, and skin when administered intravenously; in this case, hematological or immunological toxicity was not observed [7]. In another study, at the same administration mode, the functional MWCNTs were found in the liver, kidney, and spleen, from which they were eliminated mainly in 4 days [6]. By magnetic resonance imaging, it was shown that, after intravenous injection to rats, SWCNTs are accumulated in the spleen (up to 7 days), liver (up to 2 days), and kidneys (up to 5 days), but not in the lungs and blood [8].…”
Section: Discussionmentioning
confidence: 75%
“…CNTs can be accumulated in various tissues at different administration modes, but most commonly in the spleen and liver [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[13] However, it is still controversial whether these tissues are damaged. [5,7,8,14,15] ENMs in different organs could be taken into cells through endocytosis, phagocytosis, micropinocytosis, or diffusion. [16,17] After cellular internalization, NPs either assemble in intracellular vesicles (endosomes or lysosomes) or freely distribute in cytoplasm, [18] and a small portion of them (e.g., La 2 O 3 , CuO) may elicit hazard biochemical signals (e.g., oxygen radical generation, [19] cellular redox changes, [20] enzyme inactivation [21] ) and cytotoxicity.…”
Section: Doi: 101002/smll201907663mentioning
confidence: 99%
“…For the biomedical applications of ENMs, intravenous injection is a conventional route for the administration of nanomedicines or nanosized imaging agents. [9,15] When ENMs in fluids are introduced directly into the vein, the particles may first react with biomolecules in circulation, such as proteins, lipids, and amino acids to form a thin layer binding on surfaces, namely "corona" structures ( Figure 2D). These interactions may influence the circulation times, cellular uptake, immune responses, biodistribution, clearance, and metabolism of ENMs.…”
Section: Intravenous Injectionmentioning
confidence: 99%
“…Xu et al reported that, simply adding GdCl 3 to the solution mixture containing a carbon source(citrate acid) and passivating agent (ethanediamine) create better MRI agents than DTPA linked Gd particles because of high loading, with its quantum yield efficiency unchanged 42. Li et al worked with multiwalled carbon nanotubes (MWCNTs) of diameter 40–60 nm and showed that those tubes can be oxidized to introduce carboxylic groups on the surface to attach with Fe(III) ions and later link with SPIONs through solvothermal procedures 43. These MWCNTs now can be analyzed through MRI along with fluorescence, therefore giving better details about the in vivo biodistribution and clearance even 30 d after injection.…”
Section: Functionalization To Enhance Imagingmentioning
confidence: 99%